Economy, culture, and civil war in Sri Lanka - Winslow, Deborah, 1947-; Woost, Michael D., 1955- (Indiana University Press, 2004)
This title is an examination of the everyday economy, experiences, and livelihoods in the context of Sri Lanka's civil war. It argues that the war is grounded not just in the goals and intentions of the opposing sides, but also in the everyday orientations, experiences, and material practices of all Sri Lankan people.